2018
DOI: 10.1055/s-0043-124081
|View full text |Cite|
|
Sign up to set email alerts
|

The size, morphology, site, and access score predicts critical outcomes of endoscopic mucosal resection in the colon

Abstract: SMSA is a simple, readily applicable, clinical score that identifies a subgroup of patients who are at increased risk of failed EMR, adverse events, and adenoma recurrence at surveillance colonoscopy. This information may be useful for improving informed consent, planning endoscopy lists, and developing quality control measures for practitioners of EMR, with potential implications for EMR benchmarking and training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 28 publications
6
58
1
1
Order By: Relevance
“…This study demonstrated that the local colon adenoma recurrence rate in our cohort of patients with ≥ 20-mm colon LSTs managed using cap-fitted colonoscopy with EMR and ablation of the resection edge with APC was low (4.5 %). This adenoma recurrence rate was much lower than 16.0 % to 32 % reported in the literature on traditional EMR for non-pedunculated polyps (▶ Table 3) [3,10,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 84%
“…This study demonstrated that the local colon adenoma recurrence rate in our cohort of patients with ≥ 20-mm colon LSTs managed using cap-fitted colonoscopy with EMR and ablation of the resection edge with APC was low (4.5 %). This adenoma recurrence rate was much lower than 16.0 % to 32 % reported in the literature on traditional EMR for non-pedunculated polyps (▶ Table 3) [3,10,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 84%
“…[5][6][7][8][9][10][11][12][13] Proximal polyp location has been consistently reported to increase the risk of delayed bleeding at least 2-fold. [12][13][14]29 Use of antiplatelet agents has been reported in some but not other studies. 13,14 Limited data suggest that intraprocedural bleeding and type of cautery setting may represent additional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Adenomas (tubular, tubulovillous, villous, and serrated adenomas) are defined as benign tumors. Therefore, complete resection of these is possible unless there are residual lesions at the incised margin …”
Section: Assessment Of Curabilitymentioning
confidence: 99%
“…Therefore, complete resection of these is possible unless there are residual lesions at the incised margin. [148][149][150][151]…”
Section: Adenomamentioning
confidence: 99%